2009
DOI: 10.1016/j.juro.2009.02.127
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Prostatic Biopsy Gleason Sum Under Grading

Abstract: The risk of Gleason sum under grading can be predicted to a satisfactory level using our nomogram. Predicting under grading would improve patient consulting and identify those who should consider repeat biopsy, ultimately enhancing the accuracy of prostate cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…17,21 Although the appropriate number of cores that should be obtained during a prostate biopsy has not clarified, most studies contend that 10 or more biopsy cores increase the likelihood of correct GS prediction. 19,[22][23][24] However, this was not the case in our study. No association was found between the number of cores and tumour grade prediction.…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…17,21 Although the appropriate number of cores that should be obtained during a prostate biopsy has not clarified, most studies contend that 10 or more biopsy cores increase the likelihood of correct GS prediction. 19,[22][23][24] However, this was not the case in our study. No association was found between the number of cores and tumour grade prediction.…”
contrasting
confidence: 74%
“…The association between smaller prostate volume and upgrading of the GS has been reported. 7,16,17,19 It was found that prostate volume of ≤20 mL have a higher risk for upgrade than prostate volume of >60 mL. 20 On the other hand, no correlation was found in another study when one or more histopathologic grades on needle biopsy and subsequent RP specimens were compared with prostate volume.…”
mentioning
confidence: 99%
“…Numerous studies have attempted to characterize the risk of GSU [10,11,12]. However, few studies have focused on the role of a delay between the time of biopsy and the time of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Stackhouse et al conducted a nomogram by using age, PSA, prostate volume, biopsy Gleason sum, ratio of positive biopsy core and maximum percentage of cancer in cores. The accuracy of nomogram was 72.4% [33]. Capitonio et al developed their nomograms by using PSA, clinical stage, primary and secondary Gleason score in biopsy.…”
Section: Nomograms To Predict the Gleason Scorementioning
confidence: 99%